Vehicle-bridge interaction dynamics : with applications to high-speed railways - Yang, Yeong-Bin, 1954- (World Scientific, 2004)
The commercial operation of the bullet train in 1964 in Japan markedthe beginning of a new era for high-speed railways. Because of thehuge amount of kinetic energy carried at high speeds, a train mayinteract significantly with the bridge and even resonate with it undercertain circumstances. Equally important is the riding comfort of thetrain cars, which relates closely to the maneuverability of the trainduring its passage over the bridge at high speeds.